Analysis of macroeconomic influence on composite stock price index fluctuations on the Indonesia stock exchange - Martha Racwel Patty (Indonesia Accounting Research Journal, 2025)
This research analyzes the influence of macroeconomic factors, namely the exchange rate of the rupiah against the US dollar, the 7-day BI interest rate, inflation, and money supply, on the fluctuations of the Composite Index of Stock Prices in the Indonesian Stock Exchange during the period 2018-2023. The multiple regression analysis method is used to evaluate the relationship between variables using monthly data. The research results show that the exchange rate of the rupiah has a significant negative influence on the JCI, while the 7-day BI interest rate, inflation, and money supply have a significant positive influence. At the same time, these four variables were shown to significantly influence the JCI. These findings provide information for investors, economic observers, and policymakers to understand the impact of macroeconomic dynamics on the stock market, so that they can help make strategic investment decisions.